'Actually what is happening is that these constructs are being built for us': appraising the status and future of race in progressive political struggle. Issue 5 (3rd September 2022) - Paul, Joshua
ABSTRACT: It is widely accepted that race is socially constructed. Despite this, deference to race witnesses scholarship and activism becoming complicit in the reification of race and the reproduction of its effects. Gilroy describes ''the pious ritual in which we always agree that ''race''' is invented but then are required to defer to its embeddedness in the world and to accept that the demand for justice requires us nevertheless innocently to enter the political arenas it helps to mark out'. This article engages this contention through reflection on the political deployment of race in Southhall Black Sisters. Empirical data and postracial theory extend the analysis to examine an applied postracialism and to consider whether we have arrived at a new antiracist conjuncture. Ultimately, this theoretically informed and empirically engaged article examines the role of race in antiracist politics and reflects on its future as a tool for performing such principled labor.